RNA Interference: A Functional Genomics Approach for Plant Disease Management - Bharat, Sutar Suhas; Sahu, Sonupriya; Sahu, Shubhranshee Sanshlishta; Mohanty, Pratyasha; Nanda, Satyabrata; Mishra, Rukmini (Asian Journal of Biological and Life Sciences)
RNA interference machinery is most widely explored by biologist for its conserved mechanism triggered by double stranded RNA (dsRNA), results in silencing of specific genes. It is a process in which small RNAs sequence of 21–30 nucleotides are produced, that regulates the gene expression in a sequence-specific manner. It is a valuable tool for functional genomic studies. Crop plants are subjected to several plant pathogens viz. fungi, bacteria and viruses which not only affect the growth and development of plants but also results in huge yield loss. Thus, plant breeders have adopted various methods to engineer disease resistant plants for effective management of plant diseases. Among them, RNA silencing or RNA interference is used as a powerful tool during past two decades for engineering disease resistant crops. Host-induced gene silencing is mostly used for preventing the plant from disease by silencing the target genes of invading pathogen. Another RNAi-based gene silencing known as (SIGS) spray-induced gene silencing is an innovative disease control strategy used successfully for dicots and monocots against disease causing fungus and past. The present review updates the RNAi technologies and discusses the different strategies that can be adapted towards plant disease management in an eco-friendly manner.
Keywords: Disease management; Gene silencing; miRNA; Plant pathogens; RNAi; siRNA